Ethics, Sustainability and the Water, Energy, Food Nexus Approach – A New Integrated Assessment of Urban Systems. (June 2016) - Hake, Jürgen-Friedrich; Schlör, Holger; Schürmann, Karin; Venghaus, Sandra
Abstract: Current global developments put increasing ecological, economic and social pressures on urban systems. The density of urban areas concentrates these pressures especially on water, energy and food (i.e., the nexus) resources as if in a 'burning glass'. The integrated assessment approach is used to frame, study and solve issues such as climate change, water and air quality, land and public health challenges, which are at the core of the nexus approach. To meet these targets, in the last few decades a wide array of assessment tools has been developed. Most of these approaches, however, pursue national or at best regional perspectives and only rudimentarily provide for considerations of local effects. In our integrated assessment approach based on the Nexus City Index we combine an ethical derivation with participatory and accounting tools to grasp and operationalize the complexity of urban areas from a bottom-up and top-down perspective in order to derive a holistic picture of the nexus challenges in urban areas.